Lipid nanoparticles (SLN (R), NLC (R)) for cutaneous drug delivery - Souto, E. B. (2015)
Solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC) are new drug delivery systems composed of physiological lipid materials and surfactants accepted by regulatory authorities for application in cutaneous drug delivery, i.e., topical, d